2015
DOI: 10.5772/60069
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of Anodic Titanium Dioxide Films Produced on Ti-6Al-4V Alloy

Abstract: Ti-6Al-4V alloy with TiO 2 coating is the most commonly selected material to construct an aortic heart valve. Wear resistance is the main mechanical property to be evaluated for this purpose. In this paper, the wear resistance of TiO 2 thin films obtained by anodic oxidation of Ti-6Al-4V is evaluated. Anodic oxidation was performed at 20 V to 70 V with a H 2 SO 4 1 M electrolyte. The samples were thermally treated at 500°C for 1 h, and crystalline phases of TiO 2 were obtained. The wear was performed in a ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Az Erlangeni Klinikai Egyetemen Christina Janko (Prof. Christoph Alexiou, University Hospital Erlangen, Section for Experimental Oncology and Nanomedicine -SEON) áramlásos citometriával Jurkat sejt tenyészetben bizonyította, hogy a poligalláttal burkolt SPION részecskék (PGA@MNP) megõrzik az antioxidáns hatást, ami a GA esetén közismert. 34 5. Ábra He-La sejt tenyészet Berlini-kék festéssel (vas kimutatás).…”
Section: Együttmûködõ Partnerek Segítségével Mtt Tesztekkel (Zupkó Isunclassified
“…Az Erlangeni Klinikai Egyetemen Christina Janko (Prof. Christoph Alexiou, University Hospital Erlangen, Section for Experimental Oncology and Nanomedicine -SEON) áramlásos citometriával Jurkat sejt tenyészetben bizonyította, hogy a poligalláttal burkolt SPION részecskék (PGA@MNP) megõrzik az antioxidáns hatást, ami a GA esetén közismert. 34 5. Ábra He-La sejt tenyészet Berlini-kék festéssel (vas kimutatás).…”
Section: Együttmûködõ Partnerek Segítségével Mtt Tesztekkel (Zupkó Isunclassified
“…Then, a TiO 2 film was deposited on the worn steel surface, which enhanced the wear resistance of the worn surface. 23 …”
Section: Resultsmentioning
confidence: 99%
“…16,30,46 In our lab, this method has been used to evaluate wear resistance using a spherical diamond ball 10 lm in radius oscillating at 30 Hz on the flat samples (bare or coated substrates) with an amplitude of 4 mm and loads ranging from 1 g f to 20 g f . 30,47,48 The wear maps obtained for the different samples tested showed that the coatings generally present a transition from mild-to-severe wear regime at a load of 5 g f for anodic coatings and of 7 g f for sol-gel coatings. 30,47,48 Also, crystalline coatings were more resistant than amorphous coatings, a fact explained by the higher hardness of the crystalline coatings.…”
Section: Coating Adhesionmentioning
confidence: 95%
“…17,30 In addition, we obtained partial crystallization of amorphous thin films by heat treatment for 1 h at 500°C and 600°C, which resulted in a mixture of anatase and rutile phases. 30,33 The best films for hemocompatible applications were obtained with heat treatment at 500°C. 30,33…”
Section: Anodic Oxidationmentioning
confidence: 99%
See 1 more Smart Citation